PELAKSANAAN PELAYANAN PUBLIK (Studi Kasus Pelayanan Administratif di Kantor Desa Kotabaru Seberida Kecamatan Keritang Kabupaten Indragiri Hilir) - Risna "; Mimin Sundari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Public service in administrative management at Kotabaru Seberida Village Office is not yet optimal. Not optimal public service in Kotabaru Seberida Village Office caused by not implemented SOP (Standard Operational Services) that have been set.In this study the authors use the theory L.P Sinambela (2006) which consists of transparency, accountability, conditional, participatory, equality of rights, and the balance of rights and obligations. The type of research is descriptive qualitative research method.The result of the research shows that public service in administrative management at Kotabaru Seberida Village Office has not been optimal. The not optimal public in Kotabaru Seberida Village Office is caused by the not being implemented SOP (Standard Operational Services) that have been set.Keywords: Service, Public Administration, Optimal Service